Compliance with COVID-19 Preventive Measures and Associated Factors Among Women Attending Antenatal Care at Public Health Facilities of Debre Berhan Town, Ethiopia - Silesh M; Demisse TL; Taye BT; Desta K; Kitaw TM; Mekuria AD; Tafesse TT; Fenta B (Dove Medical Press, 2021)
Mulualem Silesh,1 Tesfanesh Lemma Demisse,1 Birhan Tsegaw Taye,1 Kelem Desta,1 Tebabere Moltot Kitaw,1 Abinet Dagnaw Mekuria,2 Tiwabwork Tekalign Tafesse,3 Belete Fenta4 1Department of Midwifery, College of Health Science, Debre Berhan University, Debre Berhan, Ethiopia; 2Department of Public Health, College of Health Science, Debre Berhan University, Debre Berhan, Ethiopia; 3School of Nursing, College of Health Science, Wolaita Sodo University, Wolaita Sodo, Ethiopia; 4School of Midwifery, Faculty of Health Science, Jimma University, Jimma, EthiopiaCorrespondence: Mulualem Silesh Email sileshmulualem22@gmail.comBackground: Coronavirus disease-2019 (COVID-19) is a highly contagious and cause for the death of many people worldwide. Due to physiological immunosuppressive state and mechanical alteration, pregnant women are at a higher risk of severe illness and adverse maternal and fetal outcomes from COVID-19 than non-pregnant women. Compliance with the preventive measures is essential to control COVID-19 related consequences. Therefore, this study aimed to assess compliance with COVID-19 preventive measures among pregnant women attending antenatal care at public facilities of Debre Berhan town, Ethiopia.Methods: A facility-based cross-sectional study was conducted from May 1 to 30, 2021 among 402 pregnant mothers. Data were collected via a face-to-face interviewer-administered questionnaire. Then, entered into Epi-Data version 4.6 and exported to SPSS version 25 for data analysis. In multivariable logistic regression analysis, variables with p < 0.05 were declared as statistically significant and the strength of statistical association was measured by adjusted odds ratio (AOR) and 95% confidence interval (CI).Results: Of the total 396 participants, 222 (56.1%) of women had a good compliance with COVID-19 preventive measures. Maternal age (25- 34 years) [AOR: 1.926; 95% CI (1.084, 3.421)] and (≥ 35 years) [AOR: 3.018; 95% CI (1.53, 5.952)], husband educational status [AOR: 3.68; 95% CI (1.55, 8.737)], had current chronic disease [AOR: 2.516; 95% CI (1.297, 4.883)], and knowledge [AOR: 5.484; 95% CI (3.057, 9.838)] were significant predictors to have good compliance with COVID-19 preventive measures.Conclusion: Although COVID-19 is a global and national agenda, compliance towards its preventive measures was not sufficient enough. Therefore, scale-up the community awareness via media campaign is crucial which will eventually improve compliance. Furthermore, those women who had no pre-existing chronic diseases and those in the young age group should be given special consideration.Keywords: antenatal care, compliance, COVID-19, Ethiopia